Repeated electromyography measures of leg muscles during force- controlled submaximal multi- joint leg extensions. Implications on the development of an EMG-controlled feedback control system - Reiner, A. (Leipziger Sportwissenschaftliche Beiträge, 2014)
This study was accomplished as a foundation for the development of an Elec-tromyography (EMG) -controlled feedback system for multi-joint leg exten-sions. Ten subjects performed 15 submaximal multi-joint leg extensions in a motor driven leg press and had to maintain these isometric extensions for a time period of 30 seconds. Visual force- feedback was shown on a screenwhile EMG was recorded from nine different leg muscles. Correlation, ANOVA and exploratory factor analysis were used to obtain muscular activation patternand revealed that Musculus (M.) gastrocnemius lateralis and M. vastus lat-eralis are appropriate for an EMG- controlled feedback system in order to rep-resent leg extension muscles.